IMPACT OF ENVIRONMENTAL COSTS, ENVIRONMENTAL PERFORMANCE AND ENVIRONMENTAL DISCLOSURE ON COMPANY VALUE IN BASIC MATERIALS SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR PERIOD 2017-2019 - Winnie Savira; Sri Handayani; Safrida Rumondang P; Iwan Lesmana, S.Kom, MM (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2022)
This study aims to determine the effect of environmental costs, environmental performance and environmental disclosure on company value. A number of previous literatures have found a significant positive effect of the implementation of each of the three variables on company value, but the number of studies examining the impact of these three variables on company value is still limited. We build this research model based on environmental commitment, legitimacy theory and signal theory. Data testing is done by using the regression method in testing the effect of these three variables on company value. The results showed that environmental cost has significant positive impact to company value, environment performance has negative not significant impact to company value and environmental disclosure has positive impact but not significant to company value. In other result for the regression model that used in this research showed that the model can significantly predict the dependent variable.